Evolution of the Reliability of the Fully Implantable Middle Ear Transducer Over Successive Generations. Issue 4 (April 2015) - Debeaupte, Mathilde; Decullier, Evelyne; Tringali, Stephane; Devèze, Arnaud; Mom, Thierry; Darrouzet, Vincent; Truy, Eric
Abstract : Objective: To describe the reliability of the fully implantable middle ear transducer after successive technological changes. Study Design: Prospective, observational, multicenter study. Setting: Eight tertiary referral centers. Patients: One hundred twenty-three adults were implanted with one of the five successive versions of the fully implantable middle ear implant between September 2005 and July 2012. Methods: The reliability of each generation 2 years after implantation or at the maximal lifetime was reported by means of survival curves. Only technological failures were considered; non-technological failures were excluded from the analysis of reliability. Results: One hundred fifty-seven devices were implanted during the period of study. Fifteen explantations were related to non-technological problems (e.g., infections, extrusions, etc.). One hundred forty-two implants were followed in the analysis of reliability. We observed 32 technical failures at 2 years. At the maximal lifetime of follow-up, 46 implants failed. The end of the follow-up was the first of November 2012. Survival rates at 2 years were 0%, 76.1%, 84.2%, 81.8%, and 100% for each of the successive available versions, respectively. Conclusion: The reliability of the fully implantable middle ear implant improved over generations thanks to successive technological modifications that corrected the observed failures. The latest generation seems to be a reliable fully implantable middle ear implant system up to 22 months after implantation. The need to know the reliability of these active middle ear implants incites the creation of a follow-up register including patient's data and device failures to improve patient management.